TRADITIONAL GAMES MODULE THROUGH THE CONCEPT OF TEACHING GAMES FORUNDERSTANDING: DEVELOPMENT AND USABILITY FOR TEACHING AND LEARNINGFOR MALAYSIAN PRIMARY SCHOOL CHILDREN - Fadil Ibrahim, Mohamad; Hashim, HairulAnuar; Azuar Hamzah, Nurul; Yee Cheng, Kueh; Kuan, Garry (International Journal of Psychosocial Rehabilitation, 2021)
This manuscript reports on the validity and reliability process of a traditional games module developed using the Teaching Games for Understanding (TGfU) concept for Teaching and Learning (TnL) among Malaysian primary school children. The implementation and evaluation process involved material preparation, expert review, and content validation of the module. The module was reviewed by eight subject matter experts from different fields, leading to several recommendations and subsequent amendments. The revised module was then evaluated for content validity by 11 evaluators, including eight subject matter experts and three users. The evaluation process included data collection from 63 students in primary schools under the Malaysian Ministry of Education, with physical education teachers implementing the module in their classrooms. Results showed that evaluators strongly agreed or agreed on the module’s usability and presentation (Mean = 95.4%), content (Mean = 97.7%), learning materials and TnL activities (Mean = 99.0%), and language performance (Mean = 100%). The module demonstrated strong content validity (Mean = 93.9%). The teaching method, based on play-based learning, improved students’ skill mastery, promoted positive attitudes, and increased their interest in learning through teacher guidance. The TGfU concept made learning more meaningful and allowed greater student engagement. Using this module, Malaysian children were found to be more motivated and actively involved in physical activity-based learning.